‘Shoot the Boer’ – Hate Speech, Law and the Expediency of Sound - Veit Erlmann (Law Text Culture, 2020)
In recent years, “Shoot the Boer” (“Dubul’ ibhunu”), a well-known protest song from the apartheid era, experienced an unexpected revival in the streets of South Africa—and the courts. The article traces the history of the intersection of the song and the law as it meandered through an intricate topography of cases, rules and regulations ranging from the common-law crime of high treason, apartheid “anti-terrorism” and “anti-communism” law, post-apartheid constitutional law and the Broadcasting Code of Conduct. In contrast to established judicial practice where hate speech is reduced to its verbal dimension and sound serves as an expedient and abject to be invoked and discarded at will, the article focuses on sound as an equally pertinent criterion for regulating expressions such as “Shoot the Boer.”